How to draw machines - Butterfield, Moira (London , Usborne, 2001)
Updated and re-formatted into a handy pocket size text, this guide includes step-by-step instructions to help readers produce professional-looking drawings of machines. It also features advice on Read more...
Keywords: Drawing -- Technique -- Juvenile literature. Machinery in art -- Juvenile literature. Drawing -- Technique